Komisija za medicinsko etiko URI - Soča - Erjavec, Tatjana (Rehabilitacija (Ljubljana), 2017)
In Slovenia, the Medical Ethics Committees (MEC) within regional hospitals are authorized to review local noninvasive biomedical studies. Committee members are appointed upon medical director's proposal and are directly responsible to the National MEC. Since 2010, the members of the MEC at the University Rehabilitation Institute in Ljubljana have dealt with 153 internal research project proposals, theses for various degrees and study programs, and articles submitted for publication in scientific and technical journals. The majority of research in rehabilitation is based on observation, use of assessment scales or tools, and recording and assessing the use of new technological possibilities. Many researchers participating in these studies are not medical or health care experts, therefore particular attention must be paid to the ethical aspects and ensuring patient safety. Special attention is given to inclusion criteria and voluntary participation of patients, particularly in the case of reduced decision-making capacity due to the nature of the disease, data protection and integrity of individuals during video recording or using other photo documentation. The basic right of patients admitted to inpatient or outpatient rehabilitation is participation in appropriate rehabilitation programs. Because the number of suitable patients for research, especially those with rare diseases or injuries, is small, the principal task of the MEC is to protect the rights of those patients.
Keywords: Ethics; medical ethics; medicinska etika; raziskave; rehabilitacija; Rehabilitation; research; vocational rehabilitation